Analysis of training loads in Polish adolescent road cyclists in the preparatory period and their effects on physical fitness - Zajac, B.; Gaj, P.; Ambrozy, T. (Journal of Kinesiology and Exercise Sciences, 2024)
Background: Road cycling is one of the most extreme endurance sports. Professional road cyclists typically train ~20 hours per week and cover ~600 km a week. The longest 1-day race in men`s cycling can be up to 300 km while the longest multiple-stage races can last up to 21 days. Twenty to seventy accelerations are performed during a race, exceeding maximal aerobic power. Training is a crucial component of athletes` preparation for competitions. Therefore, strong emphasis should be on recording the applied training loads and monitoring how they influence aerobic and anaerobic fitness, as well as performance. The aim of the study was to analyze the training loads in the preparatory period and their effects on aerobic and anaerobic fitness in adolescent road cyclists. Materials and Methods: The study involved 23 highly trained/national elite male road cyclists. Of them, 16 athletes (age: 16.2±1.1 years; training experience: 5.0±2.1 years) fully completed all components of the study. Aerobic fitness was measured using cardiopulmonary exercise testing (graded exercise test to exhaustion), while anaerobic fitness was evaluated using the 30-second modified Wingate anaerobic test. Each recorded training session time was distributed across training and activity forms as well as intensity zones. Results: The endurance training form used in the preparatory period was characterized by low-volume (~7.7h×wk-1), nonpolarised (median polarization index 0.15) pyramidal intensity distribution (zone1~68%; zone2~26%; zone3~1% total training volume). Endurance (specific and non-specific) and strength training forms accounted for ~95% and ~5% (respectively) of the total training time. Conclusion: Low-volume, non-polarised pyramidal intensity distribution training is probably not an effective stimulus for improving physical fitness in adolescent road cyclists. Disregarding high-intensity exercises in training programs for adolescent cyclists may result in stagnation or deterioration of physical fitness.